2006
DOI: 10.1158/0008-5472.can-05-1070
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Steroid and Xenobiotic Receptor and Its Possible Target Gene, Organic Anion Transporting Polypeptide-A, in Human Breast Carcinoma

Abstract: Steroid and xenobiotic receptor (SXR) or human pregnane X receptor (hPXR) has been shown to play an important role in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
156
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(165 citation statements)
references
References 43 publications
8
156
0
1
Order By: Relevance
“…The expression of OATP1A2 messenger RNA (mRNA) and protein in breast cancer was first reported by Miki et al (61). The results from reverse transcriptase-polymerase chain reaction (RT-PCR) analyses indicated that OATP1A2 is expressed in human breast cancer tissues, but not in noncancerous breast tissues, adipose tissues, or stromal cells (61).…”
Section: Oatp1a2 (Gene Symbol Slco1a2)mentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of OATP1A2 messenger RNA (mRNA) and protein in breast cancer was first reported by Miki et al (61). The results from reverse transcriptase-polymerase chain reaction (RT-PCR) analyses indicated that OATP1A2 is expressed in human breast cancer tissues, but not in noncancerous breast tissues, adipose tissues, or stromal cells (61).…”
Section: Oatp1a2 (Gene Symbol Slco1a2)mentioning
confidence: 99%
“…Given that OATP1A2 can mediate the transport of endogenous hormonal substrates and several anticancer drugs (Table I), several investigations have examined the expression and functional impact of OATP1A2 in cancer. OATP1A2 expression was first reported in breast cancer and subsequently in additional types of cancer including colon, prostate, and bone (Table II) (6,(61)(62)(63)65). To date, the potential functional significance of OATP1A2 has been reported in breast cancer, but not in other types of cancer.…”
Section: Oatp1a2 (Gene Symbol Slco1a2)mentioning
confidence: 99%
“…It is known that E 1 -3-sulfate is an important estrogen conjugate that has a relatively long half-life in circulation. This estrogen conjugate can be readily taken up by estrogen target cells via an active transport mechanism [62,63], and the subsequent hydrolysis mediated by sulfatases to release the hormonally-active parent hormone E 1 represents an important pathway for the biosynthesis of active estrogens in the body. Therefore, it is suggested that a marked decrease of hepatic sulfatase activity may subsequently reduce the body's overall estrogenic exposure and stimulation.…”
Section: Effect Of Tcdd and Hf Diet On Hepatic Estrogen Metabolismmentioning
confidence: 99%
“…Instead, they would usually only activate those target tissues or cells most in need of estrogenic stimulation. Here, it is also worth noting that several recent studies have shown that estrogen target cells can actively transport E1-3-sulfate into the cells (38,39). Moreover, these cells may selectively adjust their ability to actively transport E1-3-sulfate into the cells to release biologically active estrogens depending on their hormonal needs.…”
Section: Which Estrogens Are Ideal For Postmenopausal Hormone Replacementioning
confidence: 92%